Assessment of cholesterol level in dental clinic patients with recurrent oral ulcers - Abdul Jabbar, Omar; Ezzat Mustafa, Basma; Syafiq Ramli , Muhammad; Zulkifli , Mohamad Saifuldin (2016)
Introduction: Oral ulcers are one of the most common complaints of the oral mucosa lesion. Ulcer is defined by damage or discontinuity of the epithelium and lamina propria which usually affects the non-keratinized or poorly keratinized surfaces of the oral mucosa. It is a multifactorial condition several predisposing factors have been suggested.